1986
DOI: 10.1190/1.1442194
|View full text |Cite
|
Sign up to set email alerts
|

The use and misuse of apparent resistivity in electromagnetic methods

Abstract: Problems and misunderstandings arise with the concept of apparent resistivity when the analogy between an apparent resistivity computed from geophysical observations and the true resistivity structure of the subsurface is drawn too tightly. Several definitions of apparent resistivity are available for use in electromagnetic methods; however, those most commonly used do not always exhibit the best behavior. Many of the features of the apparent resistivity curve which have been interpreted as physically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(54 citation statements)
references
References 16 publications
1
52
0
1
Order By: Relevance
“…The apparent resistivity was calculated through the latetime asymptotic response (Spies and Eggers, 1986). Onedimensional analysis of the TEM data was used to obtain layered models of the shallow depths.…”
Section: Observation and Datamentioning
confidence: 99%
“…The apparent resistivity was calculated through the latetime asymptotic response (Spies and Eggers, 1986). Onedimensional analysis of the TEM data was used to obtain layered models of the shallow depths.…”
Section: Observation and Datamentioning
confidence: 99%
“…This is the same data as depicted on Figure 1 s In the zone of overlap, it is much faster to use the early-time expansion as only three terms are required. When looking at ground data, other workers (SPIES and EGGERS, 1986) found that the zones of validity did not overlap. Spies and Eggers were inverting the asymptotic expressions to find the apparent conductivity from the measured voltages and their inversion formulae only included the first term of each asymptotic expansion.…”
Section: Resultsmentioning
confidence: 91%
“…A mathematical solution for the halfspace response can be used in an inversion process for estimating a halfspace apparent conductivity from the measured data (RAICHE and SPIES, 1981;SPIES and EGGERS, 1986). The faster the halfspace response can be calculated, the faster the inversion results can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the inversion is often performed with data based on impedances (or a postprocessed quantity from the impedance, e.g. the apparent resistivity [16]). …”
Section: Introductionmentioning
confidence: 99%